An Analysis of The Feminist Characters in Kate Chopin’s “The Awakening”: Analisis Karakter Feminis dalam “The Awakening” karya Kate Chopin - Nur, Dedi Rahman (Universitas Muhammadiyah Sidoarjo, 2017)
This research concerns with the analysis of feminist characters in Kate Chopin’s work. The purpose of the research is to describe the feminist characters of Kate Chopin’s The Awakening short stories by analyzing the main female characters as feminist characters and the contribution of the feminist characters to the development of the plot. The research question of this research are: how is the feminist character reflected on Kate Chopin’s The Awakening, and how do the feminist characters affect the development of the plot in Kate Chopin’s The Awakening short stories. The design of the research is a descriptive design. The finding of this research showed that from the characters existed in Kate Chopin’s The Awakening, feminist characters is Edna Pontellier. She was considered feminist from her conversation, actions of disregarding patriarchy and social boundaries toward women, an effort to complete self-rights, self-needs, and her inner thought about freedom and self-autonomy. Also, this research showed that Edna Pontellier feminist characters have a contribution to the development of the plot of the stories. Her feminist characteristics and behavior affect to the plot. The feminist characters’ thought and attitude play important in changing the mood of the characters’ action so that making the plot developed